KUALITAS DAN DAYA TERIMA SALA LAUAK DENGAN PENAMBAHAN BAYAM DAN IKAN SEGAR SEBAGAI MAKANAN ANAK BALITA - Sari, Wulan Puspita; Faridah, Anni; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2015)
The purpose of this research was to analyze the quality and the acceptability of sala lauak. This was a researchand the development study through which 6 panelists were involved. They were the lecturers teaching Culinary Arts, and Nutrition and Food Science. The object of the research was sala lauak with spinach and fresh mackerel. This research was started from finding the available recipe and developing it based on the local potential. The recipe of sala lauak develoved was validated by the panelists. The result of the third validation test showed that sala lauak was valid after the acceptance test to a group of toddlers at Tk Dharmawanita UNP. The recipes of sala lauak develoved were 125 gr rice flour, 25 gr mackerel, 5 gr spinach, 3 gr onion, 6 gr garlic, 10 gr grinded chili, 3 gr ginger, 2 gr turmeric, 5 gr leek, 2 gr turmeric leaf, 2 gr salt, 312,5 gr water, and 20 gr cooking oil. The result of the research revealed that the portion eaten by the toddlers was 90%, the part eaten by the toddlers was 90%, the toddlers’ interest toward the food was 70%, and the time needed to eat up the food was 53,4%. This result showed that sala lauak developed was preferred to the toddlers.Keywords: sala lauak, quality, acceptability, spinach, toddlers